Pembelajaran Sentra BAC (Bahan Alam Cair) untuk Mengembangkan Kreativitas Anak; Studi Kasus RA Ar-Rasyid - Ubaidillah, Khasan (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2018)
Central learning is a learning model that provides an opportunity for children to play with various rides in accordance with activities that have been designed by the teacher. Center learning aims to stimulate aspects of child development in accordance with their growth. One of the centers that are the focus of this article is the center of BAC (Liquid Natural Materials), which is learning that uses liquid natural materials as teaching materials. Learning is designed to involve children directly in making work with facilities provided by the teacher. The results of the study explained that the BAC center discussion at RA Ar-Rasyid Kartasura was carried out with four stages of footing namely the playing environment, footing before playing, footing while playing, and footing after playing. RA Ar-Rasyid Kartasura applies the BAC (Liquid Natural Materials) center to develop children's creativity.